Molecules, morphology and morphometrics of Cainocreadium labracis and Cainocreadium dentecis n. sp. (Digenea: Opecoelidae) parasitic in marine fishes - Jousson, O.; Bartoli, P. (International Journal for Parasitology, 2001)
Molecular, morphological and morphometric analyses were conducted on several samples of Cainocreadium labracis (Opecoelidae), a trematode parasitic in marine teleosts. The samples were isolated from several specimens of Dicentrarchus labrax, the type host, and Dentex dentex. The molecular analysis of complete Internal Transcribed Spacer sequences of ribosomal DNA revealed that specimens isolated from each host species form two well-defined groups, whose sequence divergence reaches 7.5%. The morphological study showed that the two groups can be distinguished by several characters, including the level of maximum body breadth, the relative position of the testes, the shape of the cirrus pouch, and the extent of the uterus. Multivariate analyses of morphometrics demonstrated consistency of most of the characters for discriminating the two groups. Our results show that C. labracis specimens isolated from D. labrax and D. dentex represent clearly distinct entities from molecular, morphological and statistical points of view, which has enabled us to describe a new species, Cainocreadium dentecis n. sp.